2009
DOI: 10.1120/jacmp.v10i4.3068
|View full text |Cite
|
Sign up to set email alerts
|

Comparing planning time, delivery time and plan quality for IMRT, RapidArc and tomotherapy

Abstract: The purpose of this study is to examine plan quality, treatment planning time, and estimated treatment delivery time for 5‐ and 9‐field sliding window IMRT, single and dual arc RapidArc, and tomotherapy. For four phantoms, 5‐ and 9‐field IMRT, single and dual arc RapidArc and tomotherapy plans were created. Plans were evaluated based on the ability to meet dose‐volume constraints, dose homogeneity index, radiation conformity index, planning time, estimated delivery time, integral dose, and volume receiving mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 36 publications
6
71
1
1
Order By: Relevance
“…5 and 6) have been implemented clinically, investigators have steadily reported plan and dosimetric comparisons for several tumor sites as compared to other modalities. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In addition to dynamic leaf motion as in dynamic-MLC IMRT, RapidArc TM (Varian Medical Systems, Palo Alto, CA) utilizes gantry rotation as well as variations in gantry speed and dose rate. Many studies have advocated that the inherent complexities of this technique require similar, but additional, commissioning and quality assurance than that of conventional IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6) have been implemented clinically, investigators have steadily reported plan and dosimetric comparisons for several tumor sites as compared to other modalities. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In addition to dynamic leaf motion as in dynamic-MLC IMRT, RapidArc TM (Varian Medical Systems, Palo Alto, CA) utilizes gantry rotation as well as variations in gantry speed and dose rate. Many studies have advocated that the inherent complexities of this technique require similar, but additional, commissioning and quality assurance than that of conventional IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study conducted by Oliver et al [32] and Nicolini et al, [33] RapidArc plans are capable of producing better conformation in PTV than IMRT plans. RapidArc plans yielded better dosimetric indices because of inherent arc therapy nature of these plans, as is evident from this study.…”
Section: Discussionmentioning
confidence: 99%
“…As repeated forward dose calculation operations involving this huge DDC matrix are needed during an optimization process, the overall computation time of VMAT optimization is prolonged. At present, with the utilization of a multi-core computer or a computer cluster, it is possible to achieve a computation time of several minutes to tens of minutes 5,6 . However, the overall planning efficiency is still low in clinical practice, as a trial-and-error process is usually needed to manual tune some parameters repeatedly for the optimization until achieving a good plan.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, beam fluence map is modulated by a multi-leaf collimator (MLC) 1,2 to yield a carefully sculpted 3D dose distribution conformal to the cancer target [3][4][5][6] . Compared with conventional Intensity Modulated Radiation Therapy (IMRT), the treatment plan optimization problem for VMAT is much more complicated.…”
Section: Introductionmentioning
confidence: 99%